Synthesis, characterization magnetic and electrical of aluminate copper ferrite (Research, Society and Development, 2021)
Currently, ferrites have been the subject of much research due to their advantages and properties that can be easily manipulated, thus being of great technological and scientific interest. Therefore, the distribution of cations and magnetic interactions highlight an important role in these materials and, therefore, have their scientific importance. The relationships between chemical composition, crystal structure, magnetic and electrical behavior were investigated in copper aluminum ferrites. The CuAlXFe2-XO4 ferrites, where x = 0.0; 0.5; 1.0, and 1.5 were obtained by the conventional ceramic method, the solid-state reaction between iron, aluminum, and copper oxides. The oxide mixture was pre-sintered for 24 hours at 800°C and then sintered at 1100°C for 8 hours. The magnetic properties were measured by a vibrating sample magnetometer and determined from the hysteresis graph, noting that it has a moderate magnetic material behavior due to the magnetization curve profile and coercivity values ​​(~223kA/m). The electrical conductivity of the pellets was obtained from voltage-by-current characteristics as a function of temperature. The electrical conductivity of the pellets was obtained from voltage-by-current characteristics as a function of temperature. The dependence of electrical conductivity with the temperature of copper aluminate ferrites with different compositions presented a semiconductor behavior and with the increase of the material resistivity with the increase of the aluminum content, it occurs due to its conductive property. It was also observed that the saturation magnetization decreases with increasing aluminum concentration, showing the behavior of a soft paramagnetic material.